THE IMPACT OF GLOBAL DIGITALIZATION ON THE UKRAINIAN LABOR MARKET DEVELOPMENT - Anatolii Rumiantsev; Lesya Pobochenko; Zoia Pichkurova; Tatiana Tolpezhnikova; Tatiana Kovbych; Dmytro Lyashov (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The article examines the labor market of Ukraine (LMU) as a systemic formation. The features of its development in the conditions of its global distribution and intensive use of digital technologies in the world economy are determined. It was substantiated the expediency of taking into account such modern trends in the development of the world, regional and domestic labor market as: a) the digitalization transformation of regional labor markets takes place, especially the European Union, b) on the global, regional and national labor markets level is the untimely legal, institutional and financial response to the adoption of appropriate measures, aimed at supporting and accelering at the implementation of innovative changes in the working conditions of highly qualified specialists, c) in Ukraine there is a decrease in the education costs effectiveness, which is concretely manifested in the training of a significant mass of insufficiently qualified specialists who cannot meet the existing demand on the national labor market, and especially their level of training does not meet world standards, d) the domestic market mechanism inability to promptly respond to the needs to improve the workforce quality in the context of new digital and technical skills of employees, e) in the conditions of the Russian Federation aggression against Ukraine, an essential feature of the domestic labor market development is a significant outflow of qualified specialists outside the borders of our country. The proposed economic-mathematical model for calculating the synthetic index of digitalization of the LMU. The calculation of the segmental index of digitalization of the LMU in its industry sector was carried out. The innovative component of LMU digitalization is analyzed, in particular, the employment and activity of technology parks, enterprises in the innovative and technical IT sphere, and IT clusters. Conclusions are presented regarding the state and prospects of optimal use of the global digitalization influence on the development of LMU.